(untitled) (Journal of Dialogos, 2026)
The rapid integration of artificial intelligence (AI) into communication systems has fundamentally transformed how messages are produced, distributed, and interpreted. AI-mediated communication no longer operates as a neutral technological intermediary but functions as a structural force that reshapes power relations, meaning-making processes, and mechanisms of control. This study aims to critically examine communication in the age of artificial intelligence by focusing on the interrelated dimensions of power, meaning, and control. Employing a qualitative approach with a critical–conceptual research design, the study analyzes theoretical literature from communication studies, critical media theory, and AI studies, alongside policy and ethical documents related to algorithmic governance. The findings indicate that AI algorithms operate as infrastructural actors that regulate visibility, legitimize certain discourses, and marginalize others through automated curation, recommendation, and moderation systems. Furthermore, the production of meaning becomes increasingly aligned with algorithmic logics of optimization and performance metrics, leading to potential homogenization and instrumentalization of communication. At the same time, AI-enabled surveillance and behavioral normalization introduce subtle forms of discipline that shape communicative practices. Although spaces of resistance and negotiation persist, they remain asymmetrical and structurally constrained. This study concludes that communication in the AI era must be understood as a contested arena of power rather than a purely technical domain, highlighting the urgent need for critical frameworks and democratic governance to preserve communicative autonomy and pluralism.